Role of the Al-Qur’an Education Park as a Tool for Fostering Religiosity Within the Framework of the Civilization Mosque - Jermanda Ridwan Kurniaji; Mutohharun Jinan; Muhammad Wildan Shohib (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study examines the role and effectiveness of the Qur’anic Education Park program in strengthening community religiosity within the framework of the mosque as a center of civilization. Using a qualitative field research approach, data were collected through in-depth interviews, participatory observation, and documentation at Masjid Al-Muttaqiin Malangjiwan. The findings reveal that the program contributes significantly to developing students’ religiosity across cognitive, affective, and behavioral dimensions through structured learning, habituation, and teacher role modeling. Various innovations, such as interactive learning and differentiated instruction, enhance student engagement and learning outcomes. However, the program’s effectiveness remains more prominent at the individual level and has not been fully integrated into broader mosque-based social and community development. Challenges include limited human resources, diverse student abilities, and low parental involvement. The study highlights the need for strengthening program integration, improving teacher capacity, utilizing technology, and enhancing collaboration with families. Overall, the Qur’anic Education Park holds strong potential as a strategic instrument for developing a holistic, mosque-based civilization.